The large scale instability and nonlinear vortex structures in obliquely rotating fluid with small scale non spiral force - Kopp, M.I.; Tur, A.V.; Yanovsky, V.V. (Вопросы атомной науки и техники, 2015)
In this paper, we find a new large scale instability which appears in obliquely rotating flow with the small scale turbulence, generated by external force with small Reynolds number. The external force has no helicity. The theory is based on the rigorous method of multi scale asymptotic expansion. Nonlinear equations for instability are obtained in third order of the perturbation theory. In this article, we explain in details the nonlinear stage of the instability and we find the nonlinear periodic vortices and the vortex kinks of Beltrami type. Знайдено великомасштабну нестійкість, яка виникає в рідині, що обертається під нахилом, у маломасштабній турбулентності. Турбулентність генерується маломасштабною зовнішньою силою з малим числом Рейнольдса. Зовнішня сила не має спіральності. Теорія побудована з використанням послідовного багатомасштабного асимптотичного методу. Нелінійні рівняння для нестійкості отримано в третьому порядку теорії збурень. Проведено детальне дослідження нелінійної стадії нестійкості та знайдено нелінійні періодичні вихори Бельтрамієвського типу та вихорові кінки. Найдена новая крупномасштабная неустойчивость, которая возникает в наклонно вращающейся жидкости с мелкомасштабной турбулентностью. Турбулентность генерируется мелкомасштабной внешней силой с малым числом Рейнольдса. Внешняя сила не имеет спиральности. Теория построена строгим методом многомасштабного асимптотического разложения. Нелинейные уравнения для неустойчивости получены в третьем порядке теории возмущений. Проведено детальное исследование нелинейной стадии неустойчивости и найдены нелинейные периодические вихри Бельтрамиевского типа и вихревые кинки.